LOCALIZATION OF THE EPITOPE IN METHAMPHETAMINE AND ITS ANTIBODY USE FOR THE DETECTION OF METHAMPHETAMINE AND BENZPHETAMINE BY POLARIZATION FLUOROIMMUNOASSAY - CHOI, MJ; CHOI, JG; PARK, JS; EREMIN, SA (MARCEL DEKKER INC, 1995)
An antibody was prepared, using a four carbon-bridged methamphetamine molecule as an immunogen in order to develop a polarization fluoroimmunoassay for urine screening of methamphetamine and benzphetamine. Also, it s binding characteristics were investigated to locate epitope sites of methamphetamine. The study showed that the antibody was highly capable of eliciting a polarization fluoroimmunoassay response. However, the detection limit was much greater for benzphetamine(0.05ppm) than for methamphetamine(0.2ppm) and weakly antibody binding was found with methamphetamine. This difference in sensitivity may reflect the similarity of benzphetamine to the immunogen used to produce the antibody. Both benzphetamine and the immunogen have a tertiary amine attached to a carbon bridges whereas methamphetamine has only a scondary amine and amphetamine has a primary amine group. The difference of crossreactivity data between phenylethylamine drugs and beta-hydroxyl phenylethylamine drugs indicates that the beta-carbon position have a major influence on the antibody interaction. Thus, the substitution of hydroxyl group on beta-carbon resulted in virtually no antibody affinity, even if a tertiary amine or secondary amine group was present in the molecule. This suggests that the beta-carbon chain plays a primary role as the epitope site with cooperative binding site of tertiary amine or secondary amine in alpha-carbon position. A hydroxyl group at the beta-carbon position plays an important inhibitory role to the antibody binding.
Keywords: AMPHETAMINE; URINE